Interaction of Tamoxifen Analogs With the Pocket Site of Some Hormone Receptors. A Molecular Docking and Density Functional Theory Study - Landeros-Martínez, Linda-Lucila; Glossman-Mitnik, Daniel; Flores-Holguín, Norma (Frontiers in Chemistry, 2018)
In this paper, the antiestrogenic properties of Tamoxifen analogues have been investigated and a theoretical report of its analogues interaction with the pocket site of some hormone receptors are presented. Analogues were generated by modification of the hydrophilic functional group of Tamoxifen by hydroxyl, amide, carboxyl and sulfhydryl functional groups, in an attempt to improve their activity and selectivity. The analogues exhibit a negative binding energy in the estrogen and progesterone receptors, which indicates a spontaneous interaction between the analogues and the pocket site in the hormone receptors. The values of the molecular polar surface area indicate that the analogues have good permeability and are strong electrophiles. The couplings showed electrostatic interactions such as hydrogen bond and $π$-$π$ interactions. According with the Lipinsky Rule of Fiveule, the four analogues presented a good biodistribution, permeability and pharmacological action on the hormone receptors. The analysis of the charge transfer suggests an enhanced oxidative damage in the estrogen receptor.